Immunocytochemical localization of kisspeptin and kisspeptin receptor in the primate testis. Issue 3 (14th March 2016) - Irfan, Shahzad; Ehmcke, Jens; Shahab, Muhammad; Wistuba, Joachim; Schlatt, Stefan
Abstract: Background: Hypothalamic kisspeptin–kisspeptin receptor signalling in primates ensures the successful progression into puberty during development and maintenance of reproductive capacity during adulthood. Human testis has been shown to express high‐to‐moderate levels of kisspeptin and kisspeptin receptor gene expression. In this study, we aimed at characterizing the localization of kisspeptin and kisspeptin receptor in adult primate testis tissue. Methods: Immunocytochemistry was performed on paraffin‐embedded testicular sections from adult rhesus monkeys and from common marmoset monkeys. Results: Kisspeptin receptor was detected in Sertoli cells in the periphery of the seminiferous tubules in adult testes of both species. In contrast, kisspeptin was not localized in the seminiferous epithelium and was detected only in the interstitial compartment of the adult rhesus monkey testis. Conclusion: Kisspeptin receptor and kisspeptin are localized in the testis of Old World and New World primates.